2020
DOI: 10.1007/s00053-020-00488-z
|View full text |Cite
|
Sign up to set email alerts
|

S3-Leitlinie: Sinus pilonidalis. 2. revidierte Fassung 2020

Abstract: Beteiligte Fachgesellschaften Deutsche Gesellschaft für Koloproktologie (DGK); federführend Deutsche Gesellschaft für Allgemein-und Viszeralchirurgie (DGAV) Chirurgische Arbeitsgemeinschaft für Coloproktologie (CACP) Berufsverband der Coloproktologen Deutschlands (BCD) Deutsche Gesellschaft für Gastroenterologie, Verdauungs-und Stoffwechselkrankheiten (DGVS) Deutsche Dermatologische Gesellschaft (DDG) 1. Einleitung und Definition Der Pilonidalsinus oder Sinus pilonidalis (pilus = Haar, nidus = Nest) ist eine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 425 publications
(220 reference statements)
0
7
0
9
Order By: Relevance
“…It has been suggested that the low number of reconstructive procedures used in real-world data is the result of a combination of a lack of formal training, particularly in flap procedures, and a lack of expertise due to many surgeons performing low-volume pilonidal sinus surgery [24]. The administrative data thus indicate that the recommendations of the S3 guideline on pilonidal sinus disease to favour flap procedures [31,32] have not been implemented in daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the low number of reconstructive procedures used in real-world data is the result of a combination of a lack of formal training, particularly in flap procedures, and a lack of expertise due to many surgeons performing low-volume pilonidal sinus surgery [24]. The administrative data thus indicate that the recommendations of the S3 guideline on pilonidal sinus disease to favour flap procedures [31,32] have not been implemented in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…This completeness does, however, only apply to cases that were treated on an inpatient basis. Contrary to diagnoses of hip fractures in adults [37] or hypertrophic pyloric stenosis in infants [15], operations for pilonidal sinus disease are on the list of procedures that may be conducted either as inpatient or office-based procedures and their methods-such as pit picking-that are specifically used for office-based procedures [38], as recommended by the S3 guideline for pilonidal sinus disease [31,32]. While it is difficult to conduct less complex inguinal hernia repair cost-covering on inpatients [39], the financial Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies erspart den betroffenen Patienten einen zweiten operativen Eingriff und verringert zudem berufliche Ausfallzeiten [13]. Die bestmögliche operative Versorgung des akut abszedierenden Sinus pilonidalis wird weiterhin kontrovers diskutiert [6,7,15].…”
Section: Hintergrundunclassified
“…Anders als in der Vergangenheit wird nicht von einer genetischen Disposition als Ursache ausgegangen, sondern als erworbene Folge von wurzelnah abgebrochenen Haaren, die in die Tiefe eindringen und eine Fremdkörperreaktion auslösen [ 5 ]. Als Prädispositionsfaktoren werden in den deutschen S3-Leitlinien eine starke Behaarung sowie übermäßige Schweißbildung angegeben [ 6 , 7 ]. Auch eine unzureichende Körperhygiene, Adipositas und eine damit assoziierte tiefe Analfalte sowie sitzende Tätigkeiten werden als begünstigende Faktoren diskutiert.…”
Section: Hintergrundunclassified